MANAGEMENT OF THE QUALITY OF AGRICULTURAL PRODUCTS IN THE AGRARIAN AI ECONOMY IN SUPPORT OF FOOD SECURITY - Tatiana N. Litvinova; Davit N. Hakhverdyan; Elena G. Popkova; Angelina I. Litvinova (International Journal for Quality Research)
Climate change, challenges in the sphere of environmental pollution, and socioeconomic and technological changes predetermined transformations of requirements for the quality of agricultural products. The vector of quality indicators shifted from the focus on the achievement of consumer qualities and support for production, export of products, and achievement of food security to eco-friendliness and accessibility. Leading countries in the sphere of agricultural production have to be also leaders in the development and implementation of the tools of the agrarian AI economy, for this allows ensuring the quality and support for food security at the national and international levels. In this paper, we demonstrated the directions for the use of the main tools of this category and determined their advantages and influence on the achievement of the quality of agricultural products. We revealed the indicators of the effectiveness of the agrarian AI economy at the level of the leading countries and regions in this sphere. The scientific novelty of this research lies in the systematisation of the directions of development of the agrarian AI economy in the leading countries and the possibilities for its transformations at the level of new players in this sector.